EKSPLORASI AIR TANAH MENGGUNAKAN METODE KONFIGURASI AUDIO MAGNETOTELURIK (ADMT) PADA DESA BUAHAN KINTAMANI - Adiana Putra, I Kadek; Husnayaen; Ayu Nirwana, Ni Kadek (Jurnal Ecocentrism, 2024)
The demand for clean water in Binyan, Buahan Village, Kintamani District, is high due to its use in drinking, sanitation, agriculture, and livestock. Identifying aquifers at specific depths can be achieved using the resistivity geoelectric method. Considering the morphology of the survey object which is one of the triangle faces of the traces of Mount Batur Purba with wavy to steep contours, Geoelectric measurements using AGR/ADMT Type 300 HT2 were chosen. This method allows its use without the need to lay cables. This tool has the capability to reach a depth of up to 300 meters below the ground surface. The purpose of this research is to interpret data using 2-dimensional modeling to detect groundwater aquifers in the study area. Based on the rock resistivity contour interpretation along a 50 m track from west to east, the optimal drilling point is recommended at a depth of 285 m below the surface, with a total well depth of over 300 m. Filters should be installed at depths of 165 m, 195 m, and 285 m to account for the lithology, distribution, thickness, and depth of the rock layers.